Relationship between grain structure and low-temperature fracture characteristics in doped-molybdenum wire - Hoshika, T.; Hiraoka, Y.; Yoo, M.K.; Choi, J. (Funtai Funamtsu Yakin Kyokai/Japan Soc. of Powder Metallurgy, 1996)
Molybdenum alloy wire doped with La2O3 of 0.2% by mass was heated in hydrogen atmosphere at temperature between 1123 and 2473K, and subjected to three-point bend tests at temperature from liquid nitrogen temperature to room temperature. Then fracture surface of the specimen failed at liquid nitrogen temperature was examined by using a scanning electron microscope and crack initiation and propagation sites were determined. Finally relationship between fracture strength and ductility at low temperatures and grain stracture was discussed. In the present study the low-temperature fracture strength and ductility were represented by two parameters, critical stress and critical temperature, respectively. Results are summarized as follows. 1) For the specimen mainly composed of fibrous structure; Critical stress decreased substantially and in contrast critical temperature increased slightly with the increase of heating temperature. Crack initiation site was the boundary transversing the fiber and then the crack propagated across the fibrous structure. 2) For the specimen mainly composed of large and elongated grain structure; Critical stress was almost unchanged but critical temperature decreased ,though only slightly, with the increase of heating temperature. The crack initiation site was the boundary of a relatively small and equiaxed grain and then the crack propagated across the large and elongated grains.
Keywords: Bending strength; Crack initiation; Crack propagation; Crystal microstructure; Ductility; Fracture toughness; Heat treatment; Low temperature properties; Scanning electron microscopy; Stress concentration; Thermal effects; Wire; Critical stress; Critical temperature; Fibrous structure; Liquid nitrogen temperature; Molybdenum alloys